Društveno-ekonomski uvjeti održivosti povratka : primjer srpskih povratnika u Hrvatsku - Mesić, Milan, sociolog (Array, 2008)
The traditional concept of the return of refugees as a one-off and fi nal act has recently been subjected to severe criticism of the theoreticians and researchers of migrations and refugeeism. It seems that in a short period of time the realisation that the return is a complex, long and multidirectional process that can become reversible at every stage has prevailed. Monitoring of returnees has soon revealed that many of them, sooner or later, set off for new migrations. It has been concluded that it is not suffi cient for the returnees to cross the border of their country once when they are returning to it, but that the return has to be successful, or sustainable. However, it was shown that the sustainability of the return is not easily determined, and especially it is not easily measured. The results of this research confi rm that socio-economic conditions, both in the objective and the subjective sense, are crucial for the sustainability of the return. The return or the restitution of property (houses, apartments or land) is important, but it is not a suffi cient condition for the permanent stay, particularly for younger and educated returnees with children. The key issue for them is employment and the perspectives of social mobility. As this is a rare resource that the returnees can count on, it is hardly surprising that primarily the elderly, uneducated, economically inactive people are (permanently) returning, mostly to smaller rural places